Evaluación de la Fermentación de Chonta (bactris gasipaes) empleando Microorganismos Fermetadores Kéfir y Levadura para la Obtención de una Bebida Fermentada. - Lima Toapanta, Byron Patricio (2019)
The objective of the research was to evaluate the application of fermenting microorganisms tales such as water and yeast kefir (Saccharomyces cerevisae) in the fermentation process of a chonta masato for 30 hours under environmental conditions. The experimental design that was applied was a 2x4 factorial arrangement under a DBCA with two repetitions. See the 8 treatments as follows T1 (5% kefir), T2 (10% kefir), T3 (15% kefir), T4 (20% kefir), T5 (5% yeast), T6 (10% yeast), T7 (Yeast 15%) and T8 (Yeast 20%). The fermentation process was evaluated by measuring pH, ºBrix, the control parameter is the control (mother sample). The pH indicator has no significance between treatments (p> 0.05). In relation to soluble solids, samples T1, T3 and T4 had the highest content of ºBrix presented significance (p <0.05). The best treatment was obtained from the statistical comparison with the control, with T4 being the sample that shows homogeneity for the pH indicator and resulted in the highest value in ºBrix 16.7. A hedonic test was performed for the best treatment, the attributes with the highest acceptability were color and texture. Subsequently, the% alcohol, total sugars and titratable acidity are analyzed, presenting significance between control and kefir 20%. It is concluded that the 20% kefir in relation to the control has significance (p <0.05). It was also determined that kefir accelerates the fermentation process with a time of 30 hours.